Electricity autoproduction, storage and billing: A case study at Dundalk Institute of Technology, Ireland. (October 2019) - Ruth, Conall E.; Byrne, Raymond; Hewitt, Neil J.; MacArtain, Paul
Highlights: Half-hourly electricity generation, import and export metered on campus for one year. Clear benefit of college's wind turbine in terms of energy, cost and carbon savings. Switching to half-hourly pricing would provide further substantial economic savings. Investigated battery unsuitable for time-shifting, but promising for grid support. Abstract: Dundalk Institute of Technology (DkIT) is a third-level college in the east of Ireland with approximately 5000 registered students. The college is an autoproducer with an 850-kW wind turbine in operation on campus. In this study, DkIT's half-hourly electricity usage over the 2017/18 academic year was measured and the benefit of the wind turbine was assessed in terms of energy, cost and carbon savings. In the period studied, the college imported electricity at fixed time-of-use (TOU) rates, although an alternative billing approach that was analysed is half-hourly pricing (HHP) based on the system marginal price (SMP). Furthermore, after a sizing study, the operation of a large Li-ion battery to be used for time-shifting was modelled. Over the study year, the wind turbine was found to reduce the college's required import of electricity substantially, while also creating some export. This decreased the net electricity cost and net carbon emissions considerably. Irrespective of this, switching to HHP would also have provided further substantial economic savings. Conversely, the modelled time-shifting using the battery generated far too little revenue to cover the associated costs, although reserving the battery for use in the Irish grid-response markets appears to be an economically viable option.